Analysis of Model Tests of Rainfall-Induced Soil Deposit Landslide - JianJun Gan; Y. X. Zhang (Advances in Civil Engineering)
A large number of deposit landslides are induced by rainfall, and those with different weak layers may be subject to catastrophic failure. This research investigates the rainfall infiltration effect on the stability of deposit landslides with a weak layer at different slope angles. Four rainfall physical model tests were conducted with fixed double penetration artificial rainfall technique and dynamic sensor technologies by using the rainfall test methods as modified in the paper. Deformation and mechanics parameters, as well as water content parameters in the key position in the deposit landslide, were monitored by means of various displacement monitoring sensors, dynamic soil pressure sensors, pore water pressure (PWP) monitoring sensors, and water content sensors. The results show that, under the same rainfall conditions, the rule of displacement and mechanical changes of deposit slope with different angles are similar, that the displacement, soil pressure, and PWP are characterized by two stages of rising and falling, and that the displacement of deposit slope with weak layer remains creep after rainfall. In addition, the displacement at the rear edge of the slope with a small angle is larger than that at the front of the steep slope, but the displacement in the front of the slope is opposite. Furthermore, the slope with a smaller angle is prone to form a tensile crack in the back of the slope, and its deformation and failure have the characteristics of a progressive and thrust-type landslide. While the failure in front of a steep slope (slope angle more than 60°) occurred first, the slope failure was characterized by sudden and retrogressive modes. The mathematical analysis of the model is also conducted which shows that deformation and failure can be divided into three stages, i.e., creep inoculation, accumulation uplift, and speed-up sliding. The test results can provide a reference for the investigation, design, and assessment of similar deposit slopes.